The use of a non cultured autologous cell suspension to repair chronic ulcers - De Angelis, B (Int Wound J, 2013)
The purpose of this uncontrolled study was to evaluate the clinical effectiveness of ReCell (®) system in the treatment of chronic ulcers. From October 2011 to July 2012, 20 patients, 8 men and 12 women with a mean age of 70 years, with chronic ulcers of different aetiology that were unresponsive to conventional therapies were recruited and treated using the ReCell (®) system. Patient pain rate, scar aesthetics and patient satisfaction were assessed using a Visual Analogue Scale, Manchester Scar Scale and the Rosenberg Self‐Esteem Scale, respectively. Complete ulcer healing, defined as 100% reepithelialisation was observed between 40 and 60 days in 14 patients (70%) depending on the type of ulcer and comorbidity. At day 60 postprocedure, 80% reepithelialisation was present in five patients (25%), while one patient with concomitant psoriasis had 50% reepithelialisation. Pain scores improved by day 7 postprocedure. The function and aesthetics of the ReCell‐treated patients were good. It is concluded that the ReCell technique may have provided the regenerative tissue stimulation necessary for the rapid healing of chronic ulcers, including those not responsive to more traditional methods.